THE HYPOTHESIS OF THE INTERDEPENDENCE OF THE INCIDENCE OF MEDICAL PROFESSIONALS AND THE SYNDROME OF PROFESSIONAL-PSYCHOLOGICAL DISADAPTATION - A. D. Golmenko; V. P. Ilyin; V. A. Khaptanova; E. L. Vygovskiy (Acta Biomedica Scientifica, 2016)
The impaired adaptation is a dynamic condition, structurally comprising the combination of independent components: the syndrome of professional-psychological disadaptation (SPPD) (psychological component), morbidity (somatic component), and psychosomatics, including the interaction of the above components. Thus, a psychological component is the initial phase, and a somatic one, to a more marked degree, leading to further disruptions in the increase of psychological disorders and morbidity, i.e. disadaptation. The study found that the highest rates of the syndrome of professional psychological disadaptatiion are noted in the group with work experience of 0-5years. The cause is a long period of not working in their specialty, which leads to a decrease in self-regulation, psychological defenses, general theoretical and practical professional level. Preventive work in the organization should focus on psychological trainings, refresher courses or the introduction of mentoring.